Mergers and Acquisitions in the Nigerian Industries: Challenges and Solutions - Adu, Cecilia Adurayemi (Indonesian Journal of Banking and Financial Technology, 2024)
The challenges and solutions to issues surrounding mergers and acquisition in Nigeria were investigated by this study. The descriptive (qualitative) method was adopted by this study in reviewing recently done researches by diverse authors. The study discovered that Mergers and Acquisitions are strategic tools for effective and efficient growth in business organization; there would be improved turnover for organizations. It was suggested that mergers and acquisitions should be properly carried out and not in desperation in order to achieve success.